Topical Therapy in Atopic Dermatitis Patient - Wahyunita Desi Ratnaningtyas; Marsudi Hutomo (Faculty of Medicine, Universitas Airlangga, 2016)
Background: Atopic dermatitis (AD) is an inflammation skin disorder characterized by itchy, chronic, residif, can occur in infant, child, and adult. The therapy for AD are divided into systemic and topical therapy. Topical therapy is the first line therapy for mild and moderate AD which are the most common type AD. Purpose: To evaluate the pattern of topical therapy in new AD patients. Methods: Retrospective study methods was performed by evaluating medical records of new AD patients who received topical therapy in Allergy Immunology Division, Department of Dermatology and Venereology, Dr. Soetomo General Hospital from 2013 until 2015. The evaluated data included the patient's visitation, age, gender, time visit, patient's complaint, periode of illness, history of atopy, physical examination, management, and follow up. Results: There were 272 patients (83.2%) of 327 new AD patients who received topical therapy. Topical therapies were provided in form of corticosteroid topical for 187 patients (23.6%), emolient for 183 patients (23.1%), and topical antibiotic for 40 patients (5.1%). Patients who did not return to the hospital after first visitation were 174 patients (53.2%). Conclusion: Corticosteroid topical is the first line therapy for atopic dermatitis, but emolient is important to improve skin barrier.